Answer:
The result is 1
Step-by-step explanation:
we have
[tex]sec^{2}(26\°)-cot^2(64\°)[/tex]
Remember that
[tex]cot^2(64\°)=\frac{cos^2(64\°)}{sin^2(64\°)}[/tex]
[tex]sec^{2}(26\°)=\frac{1}{cos^2(26\°)}[/tex]
If two angles are complementary ----> A+B=90°
then
cos (A)=sin(B)
In this problem 26° and 64° are complementary angles
therefore
[tex]\frac{1}{cos^2(26\°)}=\frac{1}{sin^2(64\°)}[/tex]
substitute
[tex]\frac{1}{sin^2(64\°)}-\frac{cos^2(64\°)}{sin^2(64\°)}[/tex]
[tex]\frac{1-cos^2(64\°)}{sin^2(64\°)}[/tex]
we have that
[tex]1-cos^2(64\°)=sin^2(64\°)[/tex]
substitute
[tex]\frac{sin^2(64\°)}{sin^2(64\°)}=1[/tex]